Analisis Manajemen Persediaan Bahan Baku pada Angkringan dari Anyer Serang Banten - Muchamad Rohim Rivai; Restu Hidayat; Saepulloh Yusup; Saiful Umam (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
MSME business activities have workflows that meet standardization. One of the things angkringan.anyer does is carry out a raw material inventory procedure program. The aim of this research is to explain the procedure for supplying raw materials at angkringan.anyer. This research was conducted using a qualitative approach through data collection techniques in the form of observation, interviews and documentation studies. The results of this research show that the raw material inventory procedure at angkringan.anyer starts from shopping for raw materials located at Pasar Baru Anyer, as well as checking the availability of raw materials at Pasar Baru Anyer. to making a list of raw materials, providing a purchasing budget, ordering or purchasing raw materials, to making purchasing reports. Overall, all the procedures carried out have been adapted to the conditions existing in MSME businesses so that employees can follow the procedures.